Hair-growth promoting effect and anti-inflammatory mechanism of Ginkgo biloba polysaccharides. (15th February 2022) - Li, Yingna; Sheng, Yu; Liu, Jiuyue; Xu, Guangyu; Yu, Wanwen; Cui, Qingwen; Lu, Xuechun; Du, Peige; An, Liping
Abstract: The aim of this study was to optimize the separation and purification technology of water-soluble Ginkgo biloba leaves polysaccharides (WGBP), analyze its composition characteristics, observe its hair-growth promoting effect in alopecia areata mice, clarify the polysaccharide fraction with bioactive activities, and explore its anti-inflammation mechanism. We isolated acidic polysaccharides (WGBP-A2) and purified a RG-I type polysaccharide (WGBP-A2b) with a molecular weight of 44 kDa. Results showed that WGBP-A2 could significantly increase the contents of VEGF and HGF in the skin tissue of alopecia areata mice, decrease the contents of Inflammatory factors in the serum. On a cellular level, the expressions of p-p65 and p-IκBα, TNF-α and IL-1β in HUVECs treated with WGBP-A2b were down-regulated. The bioinformatic analysis showed that the inflammation signaling pathway was significantly changed. Its specific mechanism may be related to its regulating the expression of p-p65 p-IκBα, TNF-α and IL-1β proteins in the inflammation signaling pathway. Graphical abstract: Unlabelled Image